Gestão escolar e educação especial: políticas e práticas nos Estados Unidos e Brasil - Santos, Flavio Lopes dos (2022)
This thesis aimed to analyze the interdependence of public policy on Special Education and school management in guaranteeing the right to schooling for students who are the target audi ence of Special Education in basic education schools in Brazil and the United States. To this end, an international comparative case study research was carried out, of a predominantly qualitative nature, using the analysis of normative texts (which have the status of law) and the use of inter views in both realities. To bring our analyzes closer to the reality of school management in both countries, we selected two public elementary schools: one in the Framingham district in the state of Massachusetts (USA) and another in the municipality of Serra in Espírito Santo (BR). As a data source, government websites and legislation that support Special Education were used, comparing the main concepts, the definition of the target audience, typologies and description of the main rights and guarantees provided in the legislation. In addition, in the United States, we consult the Census database, the National Center for Education Statistics (NCES) and the Massa chusetts State Department of Education or DESE (Department of elementary and secondary Ed ucation) website; in the Brazilian reality, we observed the microdata from the Basic Education school census of the National Institute of Educational Studies and Research Anísio Teixeira (In ep) and Serra Municipality's website in Espírito Santo to access to enrollment indicators. Our analysis used the classification proposed by Bowe, Ball and Gold (1992) between proposed poli cy, de facto policy and policy in use and on school management used in the organization pro posed by Polon (2009) between organizational, relational and pedagogical management. The time frame for data analysis was the year 2020-2021 (August 2020 to June 2021) for the United States and 2020 for Brazil (January to December) and the interviews carried out remotely with professionals from selected public schools. The data were analyzed from the perspective of the figurational sociology of Norbert Elias (1897-1990). From this theoretical-methodological per spective, we extract the relationship of interdependence between the individual and society (there is no me without us), the power relations in the social fabric that is constantly changing and its figurations; the importance of the civilizing process in the established-outsiders relationship. For a better understanding of the social game in each social habitus on school management and mate rialization of the Special Education public policy, we sought to identify the networks of interde pendence between the government, schools, school management, professionals, students with disabilities and families. From the data, it was observed that the two social habitus researched decentralize the responsibility of offering a free public basic education, but they differ in the or ganization of their competences. The United States approaches Special Education as a service with stages, tools and deadlines defined by federal law and Brazil as a teaching modality that allows each responsible entity to organize the provision of care. The normative texts of Special Education policies present main concepts and guarantees to those who are eligible and their families, but the United States covers a larger list of typologies compared to the reality in Brazil. School management in both countries presented conflicts/tensions in the materialization of Spe cial Education in relation to the initial and continuing training of school managers and profes sionals, difficulty in aligning demand with available human resources, interdependence between professionals and the power relationship with the families of students with disabilities. Intersec toriality is a reality in the United States and in Brazil it still depends on public policies for its proper implementation.